Screening newborns for metabolic disorders based on targeted metabolomics using tandem mass spectrometry - Hye-Ran Yoon (Korean Society of Pediatric Endocrinology, 2015)
The main purpose of newborn screening is to diagnose genetic, metabolic, and other inherited disorders, at their earliest to start treatment before the clinical manifestations become evident. Understanding and tracing the biochemical data obtained from tandem mass spectrometry is vital for early diagnosis of metabolic diseases associated with such disorders. Accordingly, it is important to focus on the entire diagnostic process, including differential and confirmatory diagnostic options, and the major factors that influence the results of biochemical analysis. Compared to regular biochemical testing, this is a complex process carried out by a medical physician specialist. It is comprised of an integrated program requiring multidisciplinary approach such as, pediatric specialist, expert scientist, clinical laboratory technician, and nutritionist. Tandem mass spectrometry is a powerful tool to improve screening of newborns for diverse metabolic diseases. It is likely to be used to analyze other treatable disorders or significantly improve existing newborn tests to allow broad scale and precise testing. This new era of various screening programs, new treatments, and the availability of detection technology will prove to be beneficial for the future generations.